A new unified constitutive model for natural clay and sand - AL-Sarri, Hussein A. H. (2019)
Over the last decades, with the increase of constructions and buildings on soft soil with low bearing capacity, the need for a comprehensive tool to demonstrate the complicated response of soil under different loading conditions increases. To understand the behaviour of soil precisely, numerical analyses are used to predict the responses of geotechnical structures after incorporating more realistic constitutive models for soil behaviour. Despite the large number of modifications proposed to the standard Cam-clay model over the last three decades, these types of models still have not been very successful in modelling many of the characteristic features of heavily consolidated clays. The main objective of this research is to develop a unified constitutive model that considers different soil features and is more practical to use in the field of geotechnical engineering and more representative of natural clay and sand. This model can be used for foundation modelling. The main advantage of the new versions of the proposed model is that a single yield surface “as formulated with a general plastic potential function” is used to model the behaviour of clays and sands under both drained and undrained loading conditions. Constitutive modeling of both clays and sands behaviour for the two sides of the critical state line will be an appropriate rule, showing that the relationship of stress-dilatancy is satisfied within the formulation of the unified constitutive model to predict the behaviour of the soil. The validity of the theoretical assumptions introduced in the new models will be shown against several experimental data for both clays and sands, collected from the literature. In general, it is shown that the overall stress-strain responses of a number of natural clays, Ottawa and Portaway sand under various stress paths, can be predicted by the new model and its extensions.